Ensino de soluções químicas em rotação por estações: aprendizagem ativa mediada pelo uso das tecnologias digitais - Serbim, Flávia Braga do Nascimento (2018)
The present work is the result of an investigation on the use of the methodological proposal of rotation by stations (BACICH, TANZI NETO, TREVISANI, 2015) in the teaching of chemical solutions, with 30 second year high school students integrated to the professional training of the Institute Federal University of Alagoas, in the city of Maceió. Understanding that this proposal of methodological intervention could contribute to the teaching and learning process of Chemistry, we defined by objective: to analyze the results of the experience / intervention of a proposed didactic sequence based on the methodology of rotation by stations, mediated by the use of digital technologies, to promote active learning of concepts associated with the teaching of chemical solutions. To carry out the research, we adopted the assumptions of the qualitative approach (YIN, 2016), which defines action research (BARBIER, 2002) as the type of research most appropriate to our intervention. The data were collected through questionnaires, classroom observation, recordings of student subject interactions during classes, activities performed at learning stations, and production of conceptual maps (MOREIRA, 2010). We argue that adherence to the methodological proposal of rotation by stations contributed to the process of constructing the learning of the concepts of chemical solutions in a more interactive way. And, it allowed us to experience in learning stations other ways of approaching conceptual content beyond the more traditional practices. Thus contributing to a change of curricular practices in the process of teaching Chemistry, foresting the promotion of a more active and dynamic learning.